TSH effects on thermogenesis in rat brown adipocytes. (15th March 2015) - Martinez-deMena, Raquel; Anedda, Andrea; Cadenas, Susana; Obregon, Maria-Jesus
Highlights: Tshr is expressed in brown adipocytes and is regulated by insulin, TSH, T3 and NE. TSH increases basal and T3-stimulated Ucp1 and Dio2 mRNA and inhibits leptin mRNA. TSH increases D2 activity in T3-treated cells, inhibiting in NE+T3 treated cells. TSH activates Akt and Erk phosphorylation. TSH increases O2 consumption, confirming the role of TSH in thermogenesis. Abstract: TSH receptor (TSHR) is present in the thyroid and other tissues, as adipose tissue. In brown adipose tissue (BAT) TSH increases UCP1 expression and lipolysis. We have studied the regulation of Tshr mRNA expression and the effect of TSH on Ucp1 and Dio2 mRNA, on D2 activity and O2 consumption in rat brown adipocytes and the TSH signaling pathways. Tshr increased during brown adipocyte differentiation, was up-regulated by insulin and low TSH concentrations and down-regulated by high TSH concentrations, T3 and/or NE. TSH increased basal Ucp1 mRNA in a dose-dependent way acting synergistically with T3, while had no effect when NE was present. High TSH concentrations increased basal Dio2 mRNA (12-fold) and were synergistic with T3 (100-fold), but decreased Dio2 mRNA in T3+NE-treated cells. TSH increased D2 activities in T3-treated cells and inhibition of ERK pathway decreased the TSH effect by 55%. In T3+NE treated-cells TSH decreased D2 activity by 50%, in a dose-dependent manner. TSH activated Akt and Erk phosphorylation, while inhibition of PKA promoted Akt phosphorylation. TSH inhibited leptin mRNA. TSH increased O2 consumption by 20% and T3 enhanced its effect. Tshr is expressed in brown adipocytes and is regulated by insulin, TSH, T3 and NE. TSH increases basal and T3-stimulated Ucp1 and Dio2 expression and D2 activity only when T3 is present, but decreases Dio2 mRNA and D2 activity stimulated by NE+T3. TSH increases O2 consumption, confirming the role of TSH in the maintenance of thermogenesis.